Multi-tracing of recharge seasonality and contamination in groundwater: A tool for urban water resource management. (15th September 2019) - Vystavna, Y.; Schmidt, S.I.; Diadin, D.; Rossi, P.M.; Vergeles, Y.; Erostate, M.; Yermakovych, I.; Yakovlev, V.; Knöller, K.; Vadillo, I.
Abstract: In this study, sources of recharge and contamination in urban groundwater and in groundwater underneath a forest in the same aquifer were determined and compared. Data on hydro-chemical parameters and stable isotopes of water were collected in urban and forest springs in the Kharkiv region, Ukraine, over a period of 12 months. Groundwater transit time and precipitation contribution were calculated using hydrogeological data and stable isotopes of water to delineate groundwater recharge conditions. Hydro-chemical data, stable isotopes and emerging contaminants were used to trace anthropogenic groundwater recharge and approximate sewage and tap water contributions to the aquifer. The results indicated that each spring had unique isotopic signatures that could be explained by recharge conditions, groundwater residence time, and specific mixing patterns with sewage and water leaks. Elevated nitrate content, stable isotopes of nitrate, and the presence of emerging pollutants (mainly illicit drugs) in most of the urban springs confirmed mixing of urban groundwater with sewage leaks. These leaks amounted to up to 25% of total recharge and exhibited seasonal variations in some springs. Overall, the results show that urban groundwater receives variable seasonal contributions of anthropogenic components that increase the risk to the environment and human health, and reduce its usability for drinking water production. The multi-tracing approach presented can be useful for other cities worldwide that have similar problems of poor water management and inadequate sewage and water supply infrastructure. Graphical abstract: Image 1 Highlights: Urban groundwater quality is highly impacted by sewage inputs. Stable isotopes and emerging contaminants traced sewage leakages to groundwater. Sewage contribution and nitrate content varied seasonally in urban groundwater. Natural δ18O extremes in precipitation reflected estimated groundwater transit time.